Efektivitas metode pembelajaran audio visual interaktif terhadap pemahaman Murid TK Kristen Petra 9 Surabaya - Gemiartha, Celine Morgan; Wijaya, Feysya Sandrina; Melinda, Graceline; Pertiwi, Dewi (Nur Science Institute, 2024)
The Community Service activity at the Petra 9 Christian Kindergarten in Surabaya aims to educate students regarding their needs and wants. Effective education is when the aspirations and needs of each student are met. This personalized approach is critical, as it equips students with the knowledge and skills needed to succeed in the future, make decisions, and make positive contributions to society. The initial investment in education sets the stage for lifelong learning and growth. Through this community service activity, students understand what needs and wants are, how to differentiate between them, and that they must provide for their needs before fulfilling their wants. The learning media used are interactive audiovisuals in drama, games, sharing, coloring, and handicrafts. This activity provided positive results regarding the Petra 9 Christian Kindergarten students in Surabaya’s understanding of their needs and wants. At the end of the activity, students can answer confidently about what needs and wants and which ones should be prioritized. The audiovisual media is effective in providing understanding to the Petra 9 Christian Kindergarten students.